PENGARUH PEMBERIAN JUS TIMUN (CUCUMIS SATIVUS) TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL TRIMESTER III DENGAN HIPERTENSI DIWILAYAH KERJA PUSKESMAS PULAU GADANG KABUPATEN KAMPAR - Suriani Suriani; Lisviarose Lisviarose; Meirita Herawati; Rizka Mardiya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
According to data from the World Health Organization (WHO), approximately 536,000 pregnant women die due to hypertensive disorders of pregnancy (HDP). One effort to prevent the worsening of hypertension in pregnant women is the provision of non-pharmacological therapy, such as cucumber juice. Cucumbers are effective in treating hypertension due to their potassium, magnesium, and phosphorus content. The purpose of this study was to determine the effect of cucumber juice (Cucumis sativus) on reducing blood pressure in third-trimester pregnant women with hypertension in the working area of Pulau Gadang Primary Health Center, Kampar Regency. This study employed a pre-experimental design using a one-group pretest–posttest design. The study population consisted of all third-trimester pregnant women in the working area of Pulau Gadang Primary Health Center, totaling 24 respondents. The sampling technique used was total sampling. The measurement instruments included a baby scale and observation sheets. Data analysis was conducted using univariate and bivariate analysis, processed through a computerized system, with statistical testing using the independent t-test. The results of the paired t-test showed a p-value of 0.000, indicating that p 0.05, therefore Ho was rejected and Ha was accepted, meaning that cucumber juice had a significant effect on reducing blood pressure in third-trimester pregnant women with hypertension in the working area of Pulau Gadang Primary Health Center, Kampar Regency.It is expected that this study can serve as informational material for healthcare providers, especially midwives, and the community, demonstrating that consuming cucumber juice can reduce blood pressure in pregnant women compared to using pharmacological treatment alone.Keywords: Cucumber Juice, Blood Pressure, Pregnant Women